Estado normal del superconductor [Y1-xBax](BaSr)Cu3-y(PO4)yOz - González, J. C. (2013)
We studied the normal state of the superconducting compound [Y1-xBax](BaSr)Cu3-y(PO4)y0z derivatives of YBa2Cu3O7, prepared in normal temperature and pressure conditions by magnetic susceptibility measurement in the range from 100 to 300K, where we have observed that the compounds followed the Curie-Weiss law behavior. We observed an intimate relationship among Curie-Weiss temperature, effective magnetic moment and oxygen content in the structure.